Association of Maternal Obesity and Neonatal Hypoxic-Ischemic Encephalopathy - Monaco-Brown, Meredith; Munshi, Upender; Horgan, Michael Joseph; Gifford, Jamie L.; Khalak, Rubia (Frontiers in Pediatrics, 2022)
Objective More women are obese at their first prenatal visit and then subsequently gain further weight throughout pregnancy than ever before. The impact on the infant’s development of neonatal hypoxic ischemic encephalopathy (HIE) has not been well studied. Using defined physiologic and neurologic criteria, our primary aim was to determine if maternal obesity conferred an additional risk of HIE. Study Design Data from the New York State Perinatal Data System of all singleton, term births in the Northeastern New York region were reviewed using the NIH obesity definition (Body Mass Index (BMI) ≥ 30 kg/m2). Neurologic and physiologic parameters were used to make the diagnosis of HIE. Physiologic criteria included the presence of an acute perinatal event, 10-min Apgar score ≤ 5, and metabolic acidosis. Neurologic factors included hypotonia, abnormal reflexes, absent or weak suck, hyperalert, or irritable state or evidence of clinical seizures. Therapeutic hypothermia was initiated if the infant met HIE criteria when assessed by the medical team. Logistic regression analysis was used to assess the effect of maternal body mass index on the diagnosis of HIE. Results In this large retrospective cohort study we evaluated outcomes of 97,488 pregnancies. Infants born to obese mothers were more likely to require ventilatory assistance and have a lower 5-min Apgar score. After adjusting for type of delivery and maternal risk factors, infants of obese mothers were diagnosed with HIE more frequently than infants of non-obese mothers, OR 1.96 (1.33–2.89) (p = 0.001). Conclusion Infants of obese mothers were significantly more likely to have the diagnosis of HIE.